Carbon nanotubes in cancer photothermal therapy. - Castillo, John (Innovaciencia, 2013)
Synthesis of new nanomaterials has allowed increase the range applications in biomedical fields. Within this group carbon nanotubes are one of the most important, which are cylindrical structures whose physicochemical properties have become important tools in cancer therapy. This application includes targeted drug delivery and photothermal therapy. The aim of this paper is to review the state of the art of recent studies directed to the selective destruction of cancer cells through photothermal therapy by activating carbon nanotubes with near-infrared light or radio waves. This review will also provide relevant information to the use of a new alternative therapy in diseases like cancer by using irradiated carbon nanotubes with radiation harmless to the human body.